Supporting practice based evidence in the COVID-19 crisis: three researcher-practitioners' stories. Issue 3 (2nd October 2021) - Evans, Chris; Sabucedo, Pablo; Paz, Clara
ABSTRACT: This paper describes three linked reactions to the COVID-19 pandemic, a mix of pragmatic change and reflection that can be seen as action research. Our case studies, stories, come from the UK, Spain and Ecuador and describe three different but overlapping actions all focused on making available or using online questionnaires and drawing on counselling, psychology and psychotherapy ideas and practices and technological solutions to help address the COVID-19 crisis and the lockdown. We believe these experiences have implications for our professions.